(untitled) (Journal of Governance and Development (JGD), 2018)
Indian politics in Malaysia is playing an important role in the Indian community. Malaysian Indian Congress (MIC) is the established party in the Malaysia and represent the Indian community. The role of the MIC is to serving the community. In other hand, there is other formation of Indian parties in Malaysia which is consist of Indian Progressive Front (IPF), People Progressive Party (PPP) and other minority political parties. The problem in the MIC lead to the numerous formation of parties in Indian community. This cause a lot of problems in the Indian Political parties where the Indian community lost trust to the Indian Parties. The purpose of this paper is to examine the challenges that occur in the Indian political parties in Malaysia and to identify the reason behind those challenges occur. This study will use social identity theory to analyze the data. Qualitative approach was used in this study this study through interview the politicians, academician and civil society. The thematic analysis method is used to examine and answer the research objective. This study is signiï¬cant since it gives an input about the challenges faced by the Indian political parties in Malaysia.